From Physical to Digital: Transformations in the Artistic Creation Space - Freitas, Andressa da Silva; Vasconcelos, Flávia Maria de Brito Pedrosa (Farol, 2026)
This article investigates the transformation of the studio as a space for artistic creation resulting from the shift from the physical to the digital realm, specifically in relation to the artist's creative body. It draws on experiences and theoretical reflections within the field of contemporary art, examining electronic devices—such as smartphones and tablets—that operate not merely as technological tools or digital apparatuses but function in practice as portable studios. While this accessibility expands the conditions for creation, it also reveals contradictions by enabling production in any location, including "non-places"—a concept discussed by Marc Augé (2009). The text seeks to understand how the environment directly influences the creative body, altering its behaviors and, consequently, the artworks it produces, engaging with the writings of Sandra Rey (2002), Cecília Almeida Salles (2011), and Byung-Chul Han (2015).
Keywords: poietics; studio; creation space; creative body; electronic devices